2018
DOI: 10.5194/tc-2018-38
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can ice-cliffs explain the debris-cover anomaly? New insights from Changri Nup Glacier, Nepal, Central Himalaya

Abstract: Abstract. Ice cliff backwasting on debris-covered glaciers is recognized as an important process, potentially responsible for the so-called "debris-cover anomaly", i.e. the fact that debris-covered and debris-free glacier tongues appear to have similar thinning rates in Himalaya. In this study, we assess the total contribution of ice cliff backwasting to the net ablation of the tongue of the Changri Nup Glacier over two years. Detailed terrestrial photogrammetry surveys were conducted on select ice cliffs in N… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 36 publications
(70 reference statements)
1
6
0
Order By: Relevance
“…1a). Overall, this analysis supports the observed area-independent thinning of glaciers in the Himalaya (Salerno et al, 2017;Brun et al, 2018) and the Alps (Fischer et al, 2015;Rabatel et al, 2016) as discussed above.…”
Section: Glacier Area and The Thinning Ratesupporting
confidence: 85%
See 3 more Smart Citations
“…1a). Overall, this analysis supports the observed area-independent thinning of glaciers in the Himalaya (Salerno et al, 2017;Brun et al, 2018) and the Alps (Fischer et al, 2015;Rabatel et al, 2016) as discussed above.…”
Section: Glacier Area and The Thinning Ratesupporting
confidence: 85%
“…The area-independent thinning rate of glaciers have also been observed in the Khumbu region of the Himalaya (Salerno et al, 2017). Strong evidence in favour of this trend in several glacierised regions of High Mountain Asia has recently been provided by an analysis of thinning data from more than 6000 glaciers larger than 2 km 2 (Brun et al, 2018).…”
Section: Glacier Area and The Thinning Ratementioning
confidence: 85%
See 2 more Smart Citations
“…The latest comprehensive studies on select glaciers found that debris-covered ice can exhibit less melt than clean ice (e.g. Brun et al, 2018; Sherpa et al, 2017; Vincent et al, 2016), and while regional mass balance is not entirely negative (e.g. Bolch et al, 2017; Brun et al, 2016, 2019; Kääb et al, 2012, 2015), glacier loss and slowdown are generally the dominant modern signals that have been observed (e.g.…”
Section: Contextualizing Debris-covered Ice On Mars With Debris-cmentioning
confidence: 99%